Dental implant, component for dental applications, implant system for dental applications, method for forming protective layer on surface of implantable or implant component, implantable or implant component having protective layer, and use of protective layer
The dental implant with graded oxide layers and a protective layer addresses bacterial adhesion and hydrocarbon contamination issues, enhancing osseointegration and aesthetic appearance while maintaining surface properties for effective integration.
Patent Information
- Application Number
- JP2024177995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-11-12
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Dental implants face challenges in minimizing bacterial adhesion and biofilm formation while promoting optimal soft tissue adhesion and osseointegration, with issues arising from hydrocarbon contamination during storage affecting surface properties and integration with bone tissue.
A dental implant design with graded oxide layers and surface properties, including anodized titanium surfaces, and a protective layer formation method using specific pH solutions to maintain hydrophilicity and prevent contamination during storage.
The design enhances soft tissue integration, reduces biofilm formation, and maintains surface properties for improved osseointegration and aesthetic appearance, while the protective layer ensures the implant remains uncontaminated and ready for biological integration.
Smart Images

Figure 2025004210000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental implant, a dental component, a dental implant system, a method for forming a protective layer on the surface of an implantable or implant component, an implantable or implant component and uses of the protective layer. [Background technology]
[0002] For decades, dental implants have been used successfully to replace missing or missing teeth. One of the most important challenges in implant dentistry is to modify the properties of the soft tissue attachment surface, minimizing bacterial adhesion and biofilm formation and allowing the maintenance of good oral hygiene while promoting optimal soft tissue attachment. Furthermore, another main objective is to custom-design the surface of the dental implant that comes into contact with the bone tissue. The aim here is to allow the best possible osseointegration of the dental implant. This is the very basis for the implant to function for many years and to limit post-implant complications. In addition to all the medical and biological requirements, esthetics also plays a role. The aim here is to achieve an appearance as close as possible to a natural tooth and to prevent any part of the dental implant structure from being visible.
[0003] To at least partially address the above needs, various implant structures and designs of fasteners, spacers, and prosthetic components have been presented over the years. Additionally, various substances and compositions have been proposed for use as coatings on substrates, for example, to form implant surfaces. However, as will be recognized after reading the background of this application, the human body is a fairly sophisticated and complex environment, and how to design an implant structure to overcome the problems described is not a trivially devised task.
[0004] One method of treating dental implants that has been used for bone osseointegration and has shown good results is the TiUnite® surface. The surface generally has a titanium oxide layer with a uniformly distributed pore structure with pore sizes ranging from 50 nm to 5 microns, and phosphorus is embedded within the titanium oxide. The surface roughness Sa is about 1.2 microns. The TiUnite® surface is described in detail in Jan Hall and Jukka Lausmaa, "Properties of a new porous oxide surface on titanium implants", Applied Osseointegration Research, vol. 1, pp. 5-8, 2000.
[0005] An advanced dental implant surface design is described in WO2016 / 096734A1. In that document, a dental implant (preferably a screw-shaped dental implant) exhibits a surface design that changes essentially along the longitudinal axis of the dental implant depending on the in situ environment that each of the individual parts of the dental implant contacts. Thus, the dental implant in that document has a relatively smooth surface at the coronal end of the dental implant that is easy to clean and promotes good soft tissue connection. Towards the apical end of the dental implant, the surface roughness and porosity increases and is maximized, providing a surface for optimal ingrowth and osseointegration of the jawbone tissue. The present invention and part of this disclosure are aimed at modifying and further improving that dental implant design.
[0006] In addition to the challenges that arise with implants, there are challenges that precede the above objectives. One such challenge is to standardize and control the design characteristics of (dental) implants and abutments over their shelf life. Most commercially available implants are stored in sterile packages and have a shelf life of 5 years after manufacture.
[0007] During storage, atmospheric molecules such as hydrocarbons can deposit on the implant, causing contamination. Increased deposition of hydrocarbons on titanium has been shown to correlate with a decrease in surface energy (hydrophilicity) and a decrease in the adhesion of proteins and bone-forming cells.
[0008] In the presence of critical amounts of hydrocarbons on the surface, a reduction in the biomechanical strength of the implant's osseointegration and bone-titanium integration has been reported when compared to freshly processed titanium surfaces. To prevent such potential effects on the biological performance of medical implants during storage time, packaging strategies have been developed to maintain the surface condition, such as wet or dry storage using a soluble protective layer that results in a pristine surface after extended storage times.
[0009] Storage of the implant in a wet package leads to changes in the surface properties of the implant over time (due to oxidation, formation of nanostructures, etc.) Furthermore, the nanostructures are affected by other environmental parameters such as temperature and pressure, which cannot always be controlled throughout the storage period of the implant.
[0010] For these reasons, dry storage is preferred over wet storage. A strategy can be to store samples in a controlled protective environment (i.e., inert gas). The difficulty is ensuring that the packaging remains gas impermeable throughout the storage period, and no simple controls can be implemented at the clinician's site to show that the packaging is intact.
[0011] The final approach is to protect the surface in a dry state by applying a protective layer to the implant. The protective layer is typically applied by a dip-dry process. The protective layer prevents contaminants present in the air from reaching the surface. Upon contact with bodily fluids such as saliva or blood, the protective layer dissolves, ideally exposing the original surface with its chemical and surface energy preserved.
[0012] Rupp et al., published in J Biomed Mater Res A. (February 2006;76(2):323-34), describe a study on chemical modification of microstructured titanium implant surfaces to increase surface free energy and hydrophilicity. In this paper, wet storage of the implants in a sodium chloride solution is described.
[0013] An approach that exploits this discovery is described in WO2007 / 118734A1. In this case, a dry salt layer forms a physical barrier that protects the implant surface during dry storage, and the salt is on the implant surface when implanted. For this reason, the salt is restricted to those that are easily soluble in body fluids. In all examples in WO2007 / 118734A1, a 0.15M NaCl solution in water is used.
[0014] A study on the protective effect of salt layers formed from various saline solutions of different concentrations is described in the article by Luers et al., Current Directions in Biomedical Engineering 2016;2(1):557-560. Solutions tested included solutions containing only sodium phosphate, only potassium phosphate, only magnesium phosphate, or mixed solutions of sodium and potassium chloride and sodium and potassium phosphate. One of the solutions also contained calcium chloride and magnesium chloride.
[0015] In this study, the effect of salt layers formed from such solutions of various concentrations on titanium implants on the dynamic contact angle of the implants is investigated. The worst results were obtained for solutions containing 136.8 mM NaCl, 2.7 mM KCl, 1.5 mM KH2PO4, and 8.1 mM Na2HPO4, a solution containing only sodium phosphate with a total concentration of 96 mM, a solution containing only potassium phosphate with a total concentration of 9.6 mM, and a solution containing only ammonium phosphate with a concentration of 100 mM. All other solutions / concentrations were equally good, as no change in contact angle after storage was shown for them. The pH of all solutions tested in this study containing monovalent alkali metal cations was above 7.3, while the pH of divalent cations of alkaline earth metals (Mg or Ca) containing solutions was reported to be 6.7, 6.3, 3.5, and 2.7, respectively. Solutions at pH 6.3 and pH 6.7 are reported to result in a decrease in surface energy as indicated by the dynamic contact angle, and therefore do not provide the desired protection to the full extent. Solutions at pH 2.7 and 3.5, respectively, contain only divalent Mg cations. Mg and Ca salts (alkaline earth metal salts) are generally less soluble than their monovalent counterparts (alkali metal salts) and therefore may be more difficult to dissolve. It is also reported that solutions containing only Mg salts result in poor distribution of the salt layer on the surface at concentrations as low as 10 mM, and that at higher concentrations a syrupy residue remains on the surface. The document further reports that the surface appearance differs for each salt layer and that a homogeneous film could not be obtained in all cases. These problems were especially encountered with sodium phosphate solutions.
[0016] The authors concluded that a potassium phosphate buffer with a pH of 7.6 provides the optimal system for preserving titanium implant surfaces, since it provides the best results in terms of maintaining the hydrophilicity and optical appearance of the salt layer surface.
[0017] There are concerns about possible adverse effects on biological integration that may occur in the case of salt layers optimized for maintaining the hydrophilicity and optical appearance of the surface, in particular that such layers may remain more on the implant surface, thereby hindering osseointegration, and in many cases the support structure surface of the implant is adapted to have a specific structure and surface composition, and these properties may not be able to perform their biological function if the salt layer remains completely or partially on the implant surface.
[0018] Therefore, it is preferable if the salt layer can be quickly and completely removed when in contact with liquids such as water, body fluids, saliva, etc., with a view to minimizing the risk of impairing the healing process with the remaining components of the protective layer on the implant. There is also a need for a salt layer that allows for a quick exposure of the original support structure surface of the dental implant. The support structure surface of the dental implant should have a high surface energy (hydrophilicity) after the salt layer has dissolved. Summary of the Invention
[0019] Issues to be resolved The present invention seeks to provide a dental implant adapted to be inserted into a cavity in the jawbone, which exhibits excellent tissue integration properties, soft tissue seal formation, while at the same time reducing the risk of post-implant complications, particularly resulting from harmful biofilm formation. The present invention further seeks to provide a dental implant, which facilitates easier and better cleaning of parts of the implant, particularly those parts adjacent to tissues, exposed to the buccal cavity environment, and prone to harmful biofilm formation, thereby improving dental prophylaxis, oral hygiene, and gingival health. A further object of the present invention is to provide a dental implant with improved in situ appearance and esthetics compared to conventional implants.
[0020] The present invention further provides a dental component other than a dental implant, preferably a dental abutment, which can support and improve soft tissue attachment, minimize bacterial accumulation, and provide better in situ appearance and esthetics compared to conventional components and abutments.
[0021] Furthermore, the present invention makes available an innovative implant system which achieves superior overall properties by combining the dental implant of the present invention and a component of the present invention, preferably a dental abutment.
[0022] Yet another aspect of the invention provides a method for forming a protective layer on the surface of an implant or implant component, which prevents changes in the physiochemical surface properties of said component during dry storage, and upon use, the protective layer is easily and completely removed to reveal a surface having essentially the same properties as that of an original, freshly manufactured implant or implantable component. A further related object of the invention is to provide an implantable component or implant component having a protective layer which essentially maintains the original, functionally as-manufactured surface. The use of the protective layer for dry storage of an implantable component or implant component is a final related aspect of the invention.
[0023] It is a further object of the present invention to provide a means for protecting the surfaces of implantable components and / or implant components from contamination and / or loss of hydrophilicity, such as may occur due to uptake of hydrophobic substances from the air, which means is easily accessible to provide protection, thereby allowing easy handling and storage of the protected implant, and which means can be easily and completely removed, thereby exposing the supporting structural surfaces of the implant and minimizing the risk of interference with the healing process.
[0024] The above problems are solved and the objects are achieved by the present invention as outlined below and defined in the appended claims. Specifically, the present invention provides the following configurations (1) to (44). (1) A dental implant configured to be inserted into a cavity in a jawbone and to be at least partially disposed in bone tissue when implanted, the dental implant comprising: The dental implant comprises a coronal implant region, the surface of the coronal implant region comprising: at least partially covered with an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.1 μm to 1.0 μm; Dental implants. (2) The dental implant of (1), wherein the surface of the coronal region is smooth, essentially non-porous, nanostructured, and / or exhibits an as-machined structure, in particular including the presence of turning lines from the machining process. (3) the surface of the coronal region has an average arithmetic mean height Sa ranging from 0.2 μm, preferably from 0.4 μm to 0.6 μm, preferably to 0.8 μm; and optionally The dental implant according to any one of (1) to (2), wherein the oxide layer has an average thickness ranging from 80 nm to 130 nm, preferably to 160 nm. (4) A dental implant according to any one of (1) to (3), wherein the coronal region exhibits a yellow or pink color when viewed with the human eye. (5) The dental implant is A transitional implant area; an apical implant area; a longitudinal axis extending from the coronal implant region to the apical implant region; a series of regions from a coronal end of the dental implant along the longitudinal axis to the apex of the dental implant, the series being ordered as follows: coronal implant region - transitional implant region - apical implant region; With respect to the surface characteristics of the region, the average arithmetic mean height Sa of the apical implant area > S of the transitional implant area a >Sa of said coronary implant area, the average developed interface area ratio Sdr of the apical implant region > Sdr of the transitional implant region > Sdr of the coronal implant region, - the average thickness d of the oxide layer on the implant surface in the apical implant region OX > the average thickness d of the oxide layer on the implant surface in the transition implant region OX > the average thickness d of the oxide layer on the implant surface in said coronal implant region OX , and the average phosphorus content C of the oxide layer in the periapical implant region P > the average phosphorus content C of the oxide layer in the transition implant region P > the average phosphorus content C of the oxide layer in the coronary implant region P , The dental implant according to any one of (1) to (4), wherein at least one of the following applies: (6) A dental implant according to any one of (1) to (5), wherein the surface characteristics of the apical implant region, the transitional implant region, and the coronal implant region vary stepwise or continuously, preferably gradiently, or a combination thereof, between different regions along the longitudinal axis of the dental implant. (7) - in the apical, transitional and / or coronal implant regions, the oxide layer further comprises calcium, magnesium and / or fluoride; and / or A dental implant according to any one of (1) to (6), wherein the surfaces of the apical implant region and the transitional implant region are microporous surfaces and / or comprise at least one of a bone growth initiating substance and a bone growth stimulating substance. (8) The surface of the apical implant region is -Average Sa:1.50μm±0.4μm, -Average Sdr: 187%±50%, -Average pore size: 1.5μm±0.5μm, - average oxide layer thickness d OX :9000nm±3000nm, and -Average phosphorus content C P : in the range of from 4%, preferably from 6% to 10%, preferably to 12%, at least one, preferably all of and / or The surface of the transition implant region comprises: -Average Sa:0.8μm±0.5μm, -Average Sdr: 148%±40%, -Average pore size: 1.0μm±0.5μm, - average oxide layer thickness d OX : 7000nm ± 3000nm, and -Average phosphorus content C P : in the range of from 3%, preferably from 5% to 9%, preferably to 11%, at least one, preferably all of and / or The surface of the coronary implant region comprises: -Average Sa: 0.5μm±0.3μm, -Average Sdr:16.6%±15%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120 nm ± 40 nm, and -Average phosphorus content C P : in the range of from 2%, preferably from 3% to 5%, preferably to 6%, The dental implant according to any one of (1) to (7), which exhibits at least one, preferably all, of the above. (9) The surface characteristics of the apical, transitional and coronal implant regions are at least partially achieved by anodizing, preferably The dental implant according to any one of (1) to (8), wherein the surfaces of the apical implant region, the transitional implant region, and the coronal implant region are anodized surfaces comprising the oxide layer. (10) A dental implant according to any one of (1) to (9), wherein the surface of the transitional implant region and / or the apical implant region is obtained by performing a spark anodizing treatment. (11) The substrate of the dental implant comprises titanium or a titanium alloy, preferably consists of titanium or a titanium alloy, and optionally The oxide layer on the surface of the apical implant region and the transitional implant region preferably comprises crystalline titanium dioxide in the anatase phase in the range of 70-100%, the remainder comprising rutile titanium dioxide and / or amorphous titanium dioxide, and optionally 10. The dental implant according to any one of claims 1 to 10, wherein the oxide layer on the surface of the coronal implant region mainly comprises or consists of amorphous titanium oxide, preferably the oxide layer is substantially amorphous and / or anatase-free. (12)a) the coronal implant region extends from the coronal end of the dental implant up to 2 mm ± 0.5 mm along the longitudinal axis toward the apical end of the dental implant; the transition implant region further extends along the longitudinal axis from the 2 mm±0.5 mm up to 4 mm±0.5 mm toward the apical end of the dental implant; the apical implant region extends from the 4 mm±0.5 mm to the apical end of the dental implant; or b) A dental implant according to any one of (1) to (11), wherein the coronal implant region has a length, measured from the coronal end of the dental implant along the longitudinal axis towards the apical end of the dental implant, of from 0.5 mm, preferably from 1.0 mm, more preferably from 1.5 mm, to 2.5 mm, preferably to 4.0 mm, more preferably to 6.0 mm. (13) A dental component, preferably a dental abutment, The surface of the component is at least partially covered by an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.05 μm to 0.5 μm; Component. (14) The surface of the component is at least partially obtained by an anodizing treatment, preferably 14. The component according to claim 13, wherein the surface of the component is an anodized surface including the oxide layer. (15) The component according to any one of (13) and (14), wherein the surface of the component is smooth, nanostructured, essentially non-porous and / or exhibits an as-machined structure, in particular including the presence of turning lines from the machining process. (16) The component according to any one of (13) to (15), wherein the surface of the abutment exhibits a yellow or pink color when viewed with the human eye. (17) The surface of the component has an average arithmetic mean height Sa ranging from 0.08 μm, preferably from 0.13 μm to 0.3 μm, and optionally The component according to any one of (13) to (16), wherein the oxide layer has an average thickness ranging from 80 nm to 130 nm, preferably to 160 nm. (18) The surface of the component is -Average Sa: 0.2μm±0.1μm, -Average Sdr:5.0%±5%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120 nm ± 40 nm, and -Average phosphorus content C P : in the range of from 2%, preferably from 3% to 5%, preferably to 6%, at least one, preferably all of Sa is the arithmetic mean height of the surface of the component, Sdr is the developed interfacial area ratio of the surface of the component, and d OX is the thickness of the oxide layer on the component surface, and C P The component according to any one of (13) to (17), wherein is the phosphorus content of the oxide layer. (19) The component according to any one of (13) to (18), wherein the substrate of the component contains titanium or a titanium alloy, and preferably consists of titanium or a titanium alloy. (20) A dental implant system, comprising: A dental implant according to any one of (1) to (12), The component according to any one of (13) to (19), Including, A dental implant system, wherein the dental implant and the component are configured to be connectable to each other. (21) The implant system according to (20), wherein the surface morphology and / or magnitude of the individual surface characteristics of the coronal implant region and the components are similar to each other. (22) An implant system as described in any one of (20) and (21), wherein the difference between the magnitude of the individual surface characteristics of the coronal implant region and the magnitude of the individual surface characteristics of the component is smaller than the difference between the magnitude of the individual surface characteristics of the apical implant region or the transitional implant region and the magnitude of the individual surface characteristics of the coronal implant region. (23) The implant system further comprises a dental restoration element; The implant system according to any one of claims (20) to (22), wherein the implant, the component, and the dental restoration element are combined and connected to form an assembly or a dental parts kit. (24) A method for forming a protective layer on a surface of an implantable or implant component, comprising the steps of: a) applying a solution to the surface of the component, the solution having a pH of 6.8 or less at 25° C.; and b) drying the solution applied in step a) to form the protective layer on the surface of the dental component; A method comprising: (25) The solution is H + and H3O + The method according to (24), wherein the inorganic cation is a monovalent inorganic cation other than the above, and a monovalent, divalent, or trivalent inorganic anion. (26) The monovalent inorganic cation is Na + , K + , and NH4 + is selected from the group consisting of Optionally, the monovalent, divalent, or trivalent inorganic anion is NO3 - , SO4 2- , Cl - , PO4 3- , HPO4 2- , and H2PO4 - The method according to (25), wherein the compound is selected from the group consisting of: (27) The solution contains Mg 2+ and Ca 2+ , preferably Mg 2+ The method according to (24) or (25), further comprising an inorganic divalent cation selected from the group consisting of: (28) The pH of the solution at 25° C. is lower than the isoelectric point of the surface on which the protective layer is formed; and / or The method according to any one of (24) to (27), wherein the pH of the solution is 6.5 or less, 6.0 or less, 5.5 or less, or 5.0 or less, but 0.0 or more, 0.5 or more, or 1.0 or more, such as 1.5 or more, or 2.0 or more, for example from 2.8 to 3.4, from 3.6 to 4.9, or from 3.5 to 5.5. (29) The solution contains sodium cations, the sodium cations forming 30 to 100 mol %, for example 50 to 99 mol %, of the sum of all alkali cations and alkaline earth metal cations in the solution; The method according to any one of (24) to (28), wherein the solution contains phosphate anions, hydrogen phosphate anions, and / or dihydrogen phosphate anions, and the phosphate anions, the hydrogen phosphate anions, and / or the dihydrogen phosphate anions form 30 mol % or more, for example 50 mol % or more, of the sum of all inorganic anions. (30) The solution contains magnesium ions; Preferably, the magnesium ions form 0.1 to 50 mol % of the total of all alkali cations and alkaline earth metal cations in the solution. The method according to any one of (24) to (29). (31) The method according to any one of (24) to (30), wherein the solution does not contain calcium ions, and preferably does not contain ammonium ions. (32) The method according to any one of (24) to (31), wherein the solution has a total concentration of inorganic salts of 1 to 200 mM, 2 to 50 mM, or 5 to 20 mM. (33) The method according to any one of (24) to (32), wherein the protective layer protects the implantable component or the implant component from contamination during storage. (34) The method according to any one of (24) to (33), wherein the protective layer maintains the hydrophilicity of the implantable component or the implant component during storage, and the implantable component or the implant component exhibits a water contact angle of 0 to 30° both before the application of the solution in step a) and after rinsing the component with water at 25° C. for 2 minutes and subsequently drying the solution. (35) The method according to any one of (24) to (34), further comprising a step for increasing the free surface energy of the implantable component or a component of the implant prior to or simultaneously with the application of the solution in step a). (36) The method according to any one of (24) to (35), wherein the protective layer maintains the amount of available functional groups on the surface of the implantable component or implant component during storage. (37) The method according to any one of (24) to (36), wherein the protective layer is configured to reduce carbon deposition and maintain the hydrophilicity and / or density of free / unbound hydroxyl groups on the surface of the implantable component or implant component during dry storage compared to storage without the protective layer. (38) The method according to any one of (24) to (37), wherein the implantable component or the implant component is a dental component such as a dental implant or an abutment, preferably a dental implant. (39) The method according to (38), wherein the implantable component or the implant component is an implant according to any one of (1) to (12), or a component according to any one of (13) to (19), or an implant system according to any one of (20) to (23). (40) The method according to any one of (24) to (39), wherein the implantable component or the implant component is made of a metal or a metal alloy, preferably titanium or a titanium alloy. (41) An implantable component or an implant component having a protective layer obtained by the method according to any one of (24) to (40). (42) An implantable component or an implant component having a protective layer according to (41), wherein after rinsing the implant or the component with water at 25°C for 2 minutes, not more than 30 atomic %, for example not more than 20 atomic %, preferably less than 10 atomic % of the protective layer remains on the surface. (43) Use of a protective layer obtained by drying the solution defined in any one of (24) to (32) for protecting an implantable component or an implant component from contamination during storage, comprising: Preferably, the implantable component or components of the implant are dry during storage. (44) The use according to (42), wherein the implantable component or the implant component is an implant according to any one of (1) to (12), or a component according to any one of (13) to (19), or an implant system according to any one of (20) to (23).
[0025] Further advantages and objects of the present invention will become more apparent from the following detailed description.
[0026] Detailed Description of the Invention The terms used in the following description are not intended to limit the present invention.
[0027] Any method for determining the parameters and characteristics described below may be used in addition to the methods used or standardized in the art. In case of differences or incompatibilities, the present disclosure shall prevail.
[0028] Water contact angle can be determined according to DIN55660-2. Contact angle quantifies the wettability of a surface and represents its free surface energy and hydrophilicity. The term "contact angle" refers to the contact angle of water on a surface. Measurements are carried out according to the drop method using, for example, the device EasyDROP DSA20E (Kruss GmbH) with a drop size of 0.3 μl. Contact angle can be calculated by fitting a bow function to the contour of a drop placed on the surface. The term "hydrophilic" can refer to a contact angle of 30° or less.
[0029] In the present invention, all parameters and product properties relate to those measured under standard conditions (25° C., 101 kPa) unless otherwise stated or stipulated by a specific standard or test protocol.
[0030] The term "about" means that the relevant amount or value is generally within ±5% of the indicated value, or some other value close to the specified particular value. Thus, for example, the expression "about 100" means a range of 100 ±5. All values given below are considered to be modified by the word "about" unless the context provides a different meaning or indicates otherwise.
[0031] The term "and / or" means that either all or only one of the indicated elements is present. For example, "a and / or b" means "only a," or "only b," or "a and b together." In the case of "only a," the term also includes the possibility that b is not present (i.e., "only a and not b").
[0032] As used herein, the term "comprising" is intended to be non-exclusive and open-ended. Thus, a composition or article that includes a particular component may contain other components in addition to those listed. However, the term also includes the more restrictive meanings ("consisting of" and "consisting essentially of") and is used synonymously with "made of" and "made essentially of," respectively.
[0033] Whenever a range is expressed as "from x to y," or the synonymous expression "x to y," the endpoints of the range (i.e., value x and value y) are included. Thus, the range is synonymous with the expression "greater than or equal to x, but less than or equal to y."
[0034] The various embodiments disclosed herein can be combined in any manner except where clearly incompatible, and any given range is considered to include and disclose any value within that range.
[0035] Dental implants A dental implant according to the present invention and disclosure is configured to be inserted into a cavity in a jawbone and to be at least partially located in bone tissue when implanted, and includes a coronal implant region, the surface of the coronal implant being at least partially, preferably completely, covered by an oxide layer having an average thickness in the range of 60 nm to 170 nm and having an arithmetic mean height Sa in the range of 0.1 μm to 1.0 μm.
[0036] The expression "dental implant" is broadly interpreted as an entity configured for use in human or animal dentistry. Moreover, a dental implant according to the present invention is configured to be placed at least partially inside a hole formed in the jawbone to provide a base for additional implant components to be placed and / or fixed therein. As a non-exclusive and non-limiting example, a dental implant of the present invention may be a threaded artificial tooth root, which can be threadedly, i.e., via a screw, engaged with the jawbone and extends from the oral cavity through the gums and further into the cartilage and bone tissues, and may be called a "dental screw". For ease of understanding and purely for illustrative purposes, the following description may refer to a "dental screw" as a non-limiting example of a dental implant. For example, non-threaded implants are included within the scope of the present invention. Also included within the scope of the present invention are multi-part dental implants assembled from and by several individual physical entities.
[0037] The expression "coronal", as well as all other similar terms found in this disclosure, such as "apical", should be interpreted according to the general dental-related meanings contained in those terms. Thus, a coronal implant region is located in-situ adjacent to where the crown region of the tooth at the implant site would normally be located, and an apical implant region is located away from the coronal region in a direction toward the jawbone where the root region of the tooth at the implant site would normally be located. Furthermore, the coronal and apical implant regions so described should be interpreted as indicating a "start point" and an "end point", respectively, with respect to the evolution of the implant surface characteristics as further described below. More specifically, the apical end or apex of a dental implant and the coronal end of a dental implant are points.
[0038] A dental implant has a surface that essentially forms a transition interface between a substrate associated with the dental implant (e.g., substrate / bulk material of the implant or implant coating) and the oral environment in the broadest sense. The oral environment may include, but is not limited to, specific tissues such as gingival soft tissue or various types of bone tissue. The interface may also be between the implant and the buccal cavity, i.e. essentially an interface between the implant and any possible physiological substance in contact within the buccal cavity (e.g., saliva). The contact environment depends on the region / part of the implant (coronal, apical, middle / transition) and the implantation method (e.g., embedded, flush, or extruding). The term "surface of an implant / component / abutment" or "surface of region X / Y / Z" preferably refers to the outer and outermost surfaces that define the implant relative to the oral environment as explained above. In contrast, the inner surface of a dental implant or component / abutment, e.g., an opening / cavity / hole facing the inside, is usually not exposed to the oral environment. However, in some scenarios, these inner surfaces may also benefit from the features of the present invention, especially when any exposure to the oral environment may be intentional or unintentional and therefore not excluded when considering the case. In other words, the beneficial surface properties described herein may also be applied to the inner surfaces of dental implants or components / dental abutments, as described below, and are part of the present invention.
[0039] According to the present invention and disclosure, the dental implant has a coronal implant region located at the top of the dental implant. In the technical field of the present invention, the coronal implant region is often also called "collar region", which may be considered as an equivalent term. The surface of the coronal implant region is at least partially, preferably completely, covered by an oxide layer. This includes options such as only one specific region of the surface of the coronal implant region or one of the surface regions having an oxide layer formed thereon, or even the entire coronal implant region being completely covered with said oxide layer. The latter may be preferred for functional reasons, as will be outlined later. The overall nature of the oxide layer is not particularly limited. The term "oxide layer" is to be understood as a layer that mainly comprises, consists of, or consists entirely of at least one oxide, i.e. a compound of oxygen and at least one other element. In the context of the present invention, metal oxides (Me-O), in particular titanium oxide, especially TiO2, are preferred compounds for the oxide layer. For example, an oxide layer formed by exchange of the implant material at the surface, by phase transformation or surface reaction at the implant surface, is conceivable. Such types of layers usually do not require the application of additional materials to the implant surface, but instead essentially originate from the implant substrate itself, which is exchanged / transformed by any of the known procedures. However, it is conceivable that elements from the electrolyte may be incorporated into the oxide layer, for example, in the case of an electrolytic process for forming the oxide layer. Such elements may include, for example, phosphate and / or phosphorus. Other possible types of oxide layers include layers applied to the implant surface via a coating process, where conventionally, additional materials are applied to the mostly unchanged / intrinsic implant surface or simply to the implant substrate.
[0040] Said oxide layer has a thickness in the range of 60 nm to 170 nm. The thickness of the oxide layer can be measured on an image of an axial section of the dental implant, as further detailed below. Furthermore, the surface of the coronal implant region has an arithmetic mean height Sa in the range of 0.1 μm to 1.0 μm. The parameter Sa is well known to the skilled artisan and is a standard parameter characterizing the areal roughness of a surface. Therefore, the synonymous expression used for Sa is "surface roughness" and can also be used in the present invention. The parameter Sa can be determined from white light interferometry measurements, as further detailed below. Preferably, said Sa is the average areal roughness, meaning that Sa was measured at various positions of the coronal implant region or any implant region involved and was then a mathematical average calculated from all the measurements. Furthermore, it should be noted that the surface roughness Sa described herein preferably represents the surface of the coronal implant region including the oxide layer formed on the surface. In other words, the formation of an oxide layer on the surface of the dental implant substrate determines the overall surface roughness Sa of the surface. The measured surface roughness can be considered as a superposition of the surface roughness of the surface of the substrate of the dental implant, for example created by machining, and the surface roughness of the oxide layer on the dental implant. The surface of the substrate of the original / intrinsic implant has an intrinsic roughness that is mainly determined by the method of manufacturing the bulk implant itself and its surface finish. The oxide layer formed on the dental implant surface or forming the dental implant surface also has an intrinsic roughness. As a result, the overall surface roughness is a superposition of the microscale amplitude, low frequency roughness of the as-machined / finished implant surface, and the nanoscale amplitude, high frequency roughness of the surface layer formed on the implant. Especially in the coronal implant region, the surface of the as-machined surface structure is further present / detectable and is further "decorated" by the oxide layer. In contrast, especially in the periapical implant region, where a rather thick oxide layer may be present, the as-machined surface structure of the substrate is completely filled / covered by the oxide layer and does not significantly determine the surface properties.When spark anodization is used to produce the surface, the oxide layer formed typically has a thickness of more than 5 μm and therefore masks the roughness of the as-machined surface structure.
[0041] The combination of oxide layer thickness (60 nm-170 nm) and surface roughness Sa (0.1 μm-1.0 μm) in the coronal or collar region of the dental implant (preferably the dental screw) results in the following advantageous biological and clinical effects: On the one hand, a particular oxide layer thickness results in an interference color of the coronal implant region that is yellow or pink when viewed by the human eye. The coloring is beneficial in minimizing the gray shine-through effect through the soft tissue when the dental implant is implanted. Improved soft tissue appearance can be achieved by intentionally adjusting the oxide layer thickness to change the color from the traditional metallic gray encountered in the prior art to yellow or pink. Thus, the present invention can be considered as a selection invention, where a narrow range of thicknesses was intentionally selected from the wide range of oxide layer thicknesses potentially found in the prior art, to give the coronal implant region a unique color that improves the cosmetic appearance of the dental implant once implanted. Furthermore, the presence of an oxide layer, particularly in the case of a titanium oxide layer, in the coronal implant region exhibits good biocompatibility and stimulates the attachment, proliferation, and extracellular matrix secretion of human gingival fibroblasts. Furthermore, the presence of an oxide layer may confer antibacterial surface properties. A specific minimal to moderate surface roughness can reduce marginal bone loss around implants compared to smoother as-machined surfaces. At the same time, the roughness is not chosen to be too high, which facilitates the maintenance of the implant, in particular improving its cleanability. The formation of biofilm or calculus on the surface is lower than in the case of rough surfaces, which makes the removal of biofilm or calculus by mechanical means (brushing, etc.) significantly easier. Furthermore, compared to fairly smooth surfaces, the selected surface roughness also provides good anchoring points for tissue attachment and integration. A specific oxide thickness supports these effects, since it first ensures that there is a stable and substantial oxide layer available.
[0042] Preferably, the surface of the coronal region is smooth, which exhibits an as-machined microstructure, including in particular the arrangement of lathe lines from the machining process, and which surface is essentially non-porous and / or nanostructured. The "smooth" property is primarily a qualitative way of describing the surface of the coronal implant region. A quantitative way is to define the surface roughness Sa as explained above. "Non-porous" here means that the surface of the coronal region does not exhibit a high density or a large number of open pores, which intersect the surface and create small holes thereon. "Pore" here is defined as a hole in the surface, which means a property in which the diameter of the surface is much smaller than the depth perpendicular to the surface. Thus, the surface is clearly distinguishable from the implant surface region intended for strong bone tissue connection, and thus has a highly porous morphology as explained below. "As-machined microstructure" here means that the surface of the coronal implant region exhibits a large or small number of regular "patterns" resulting from the machining or the bulk of the dental implant. Preferably, the machined structures are maintained and are detectable at the surface and are not completely hidden or filled by the surface / polymerized oxide layer. By "nanostructure" here is meant that the oxide layer exhibits nano-sized structures such as pits with diameters of less than 100 nm (e.g. golf ball-shaped pits on the surface). Thus, the surface morphology of the coronal implant region is determined by both the as-machined surface morphology and the surface morphology of the oxide layer. An example of such an as-machined surface is a turned surface which further exhibits a regular pattern of fine turning lines that are covered but not filled by the oxide layer. The turning line pattern results in an "oriented" line roughness, meaning that the line roughness is smaller along the turning lines but larger perpendicular to the turning lines and due to alternating turning lines and troughs. In other words, the surface of the coronal implant region has an oriented (line) roughness. The above-mentioned preferred properties of the surface of the coronal implant region further enhance the above-mentioned advantageous effects.In other words, the surface of the coronal implant area has both a microstructure, optionally formed by machining, preferably in the form of a lathe line pattern, and further a nanostructure resulting from an oxide layer formed on the as-machined surface. The nanostructure is characterized by nanoscale indentations, pits, spherical features, and nanoscale hilly structures. The nanostructure beneficially "roughens" the as-machined surface, otherwise making it rather smooth (overly smooth), thereby providing its desired function, in particular good tissue integration. The nanostructure is usually distinguished with respect to pores by having a diameter larger than its depth.
[0043] The surface of the coronal region may further have an arithmetic mean height Sa ranging from 0.2 μm, preferably from 0.3 μm, more preferably from 0.4 μm, to 0.4 μm, preferably to 0.6 μm, preferably to 0.8 μm, and the oxide layer may further have an average thickness ranging from 80 nm to 130 nm, preferably to 150 nm, more preferably to 160 nm. These values are preferred surface roughness ranges and preferred oxide layer thickness ranges, the lower and upper limits of which are freely combinable with each other and all values therebetween are part of the present invention and disclosure. Also, combinations of only the upper and only the lower limits are part of the present invention and disclosure. By adjusting the thickness of the oxide layer, it is possible to flexibly fine-tune the color and / or nanostructure of the coronal implant region as well as the above-mentioned biological properties, thereby making it possible to further improve them or adapt them to the individual needs of a particular condition or group of patients.
[0044] The coronal region preferably exhibits a yellow or pink color when viewed by the human eye and / or analyzed by a spectrometer. Part of the present invention and disclosure are all colors intermediate between yellow and pink in the color spectrum. As explained above, the coloring preferably results from interference colors, reducing and minimizing the gray shine-through effect due to soft tissues, thus improving the cosmetic and aesthetic appearance of dental implants and dental restorative techniques. In the present invention and disclosure, the coloring is preferably achieved by anodization, and therefore the respective methods may be called "yellow anodization" or "pink anodization" or the like. As indicated above, optionally, an oxide layer and therefore the coloring can also be provided on the inner surface of the dental implant or component, as explained below. This may contribute to better fixation of screws and the like when inserted into a cavity having said inner surface.
[0045] Preferably, the dental implant according to the present invention and disclosure further comprises a transitional implant region, an apical implant region and a longitudinal axis extending from the coronal implant region to the apical implant region, the sequence of regions starting from the coronal end of the dental implant along the longitudinal axis to the apex of the dental implant being coronal implant region-transitional implant region-apical implant region, and at least one of the following applies with respect to surface characteristics of said regions:
[0046] - average arithmetic mean height of apical implant area Sa > transitional implant area Sa > coronal implant area Sa; - average developed interface area ratio Sdr of apical implant area > Sdr of transitional implant area > Sdr of coronal implant area; - the average thickness d of the oxide layer on the implant surface in the apical implant area OX > Average thickness of the oxide layer on the implant surface in the transitional implant area d OX > Average thickness of the oxide layer on the implant surface in the coronal implant area d OX , - the average phosphorus content of the oxide layer in the periapical implant area C P> Average phosphorus content of the oxide layer in the transition implant area C P >Average phosphorus content of the oxide layer in the coronal implant area C P .
[0047] In principle, the coronal implant region described so far can be combined with any of the other freely designed regions of the dental implant. However, in order to provide the dental implant with overall superior properties, it is preferred to combine the coronal implant region with advantageous properties with other specifically designed implant regions which themselves exhibit advantageous properties. In short, this results in a dental implant which meets many design requirements necessary to achieve an overall superior implant performance in terms of biocompatibility and durability. It is therefore preferred that a transitional implant region is present between the coronal implant region and the apical implant region, and that said additional two specific regions have purposefully designed specific surfaces. The preferred implant structure has been described above. From the above description, it can be seen that the surface properties of each of the three different regions are meant to be different. In particular, there is a clear evolution of the physiochemical surface properties from the coronal implant region to the apical implant region, which includes the transitional implant region with intermediate property values. Thus, the physiochemical surface properties S a , S dr , d Ox and C P have their minimum value / magnitude in the coronal implant region and their maximum magnitude in the apical implant region. The parameter "Sdr", called the developed surface area ratio or developed interface area ratio, is a standard parameter for surface characterization and is well known to those skilled in the art. It can be determined, for example, by white light interferometry using an optical 3D profilometer.
[0048] Furthermore, with regard to dental implant structures with differently designed surfaces in different regions of the implant, please refer to WO2016 / 096734A1 (the contents of which are incorporated herein by reference). In particular, all teachings regarding the structure of the transitional and apical regions as well as the surface roughness and pore size of those regions are incorporated in that patent document. Part of the present invention and disclosure is a dental implant with the above-mentioned colored coronal implant region combined with any of the structural variations of the transitional and apical regions described in the above-mentioned WO2016 / 096734A1. In that case, the "transitional region" of the said document is equivalent to the "transitional implant region" of the present invention, and the "apical region" is equivalent to the "apical implant region".
[0049] Regarding the benefits and advantages of the above configurations, for example, the increase in Sdr from the coronal implant region to the apical implant region and apex is designed to counter the bone density profile that decreases from the implant platform to the apex. This increases friction toward the apex and allows for proper implant retention. Regarding the advantages of increasing surface roughness Sa and porosity or pore size, see WO2016 / 096734 mentioned above. The advantages described therein are equally applicable and developed in the present invention.
[0050] The "longitudinal axis" introduced above is, in the case of a dental screw or pin-like substantially cylindrical implant, the central axis of symmetry (e.g. the axial centerline of the dental screw extending along the main axis (long axis) of the dental implant), along which the coronal and apical regions are located. Assuming that the dental implant has an aspect ratio corresponding to its length being significantly greater than its width (diameter), the longitudinal axis becomes the long axis.
[0051] Phosphorus content C above P is related to the oxide layer, i.e., the phosphorus content C Pis a property of the oxide layer, measured on and from its surface. Phosphorus can result from the process by which the oxide layer is produced. If this is done by anodization, phosphorus found in the electrolyte used is incorporated into the oxide layer. In particular, phosphorus content and surface chemistry can be determined using X-ray photoelectron spectroscopy (XPS) or any other suitable method known to those skilled in the art. Having phosphorus in the surface oxide layer, preferably in the form of phosphates, increases the likelihood of improving osteoblast attachment and differentiation, improving bone healing. Phosphorus promotes osseointegration. The presence of phosphorus, which is also a constituent of bone apatite, is believed to further promote the bone tissue integration of dental implants, especially when present in the periapical implant area. It is therefore particularly preferred to have the highest phosphorus content there.
[0052] The surface properties (particularly the physiochemical surface properties of the apical, transitional and coronal implant regions) may vary stepwise or continuously / smoothly, preferably gradiently, or a combination thereof, between different regions along the longitudinal axis of the dental implant. Above several construction options are described how the evolution of the surface properties along the dental implant can be realized. On the other hand, some or all of the surface properties may vary incrementally along the longitudinal axis of the dental implant or may vary abruptly within a few micrometers along the longitudinal axis. Each of the surface properties may have its own variation profile along the longitudinal axis. In particular, uncorrelated surface properties may vary independently of each other and may show quite different variation profiles. A continuous, smooth or gradient variation increases the adaptability of the dental implant during use, since no spatially discontinuous step changes in the implant surface properties occur, which would require a more precise placement during the implant's implementation. Furthermore, the consequences of biotransformations, such as bone atrophy, are better mitigated by the continuous change in surface properties compared to implants with large abrupt changes. However, a step change can be advantageous in controlled implant scenarios where a sharp tissue interface exists and thus a sharp transition in surface properties is desired.
[0053] Preferably, in the apical, transitional and / or coronal implant regions, the oxide layer further comprises calcium, magnesium and / or fluoride. Given that said elements are also constituents of bone apatite, their presence is further believed to promote bone tissue integration of the dental implant, especially when present in the apical implant region. The incorporation of elements into the oxide layer by ion implantation or doping can improve the biological performance of the metal surface. Thus, part of the present invention and disclosure is the modification and functionalization of the oxide layer by incorporating elements and / or substances into the oxide layer that are not normally part of the oxide layer. Thus, the oxide layer can be ion implanted, ion exchanged, doped, coated and / or functionalized.
[0054] Optionally, the surfaces of the apical and transitional implant regions are microporous and / or contain at least one of a bone growth initiator and a bone growth stimulator, preferably of the superfamily TGF-beta, which can purposefully and proactively improve bone tissue integration by promoting bone cell proliferation and growth.
[0055] In certain preferred embodiments of the dental implant, the surface in the apical implant region exhibits at least one of the following, and preferably all of the following: -Average Sa:1.50μm±0.4μm, -Average Sdr: 187%±50%, -Average pore size: 1.5μm±0.5μm, - average oxide layer thickness d OX : 9000nm ± 3000nm, and -Average phosphorus content C P and / or the surface of the transitional implant area exhibits at least one of the following, preferably all of the following: from 4%, preferably from 6%, to 10%, preferably to 12%; - average Sa: 0.8 μm ± 0.5 μm, preferably 0.8 μm ± 0.3 μm, -Average Sdr: 148%±40%, -Average pore diameter: 1.0μm±0.5μm - average oxide layer thickness d OX : 7000nm ± 3000nm, and -Average phosphorus content C P and / or the surface of the coronal implant area exhibits at least one of the following, preferably all of the following: from 3%, preferably from 5%, up to 9%, preferably up to 11%: -Average Sa: 0.5μm±0.3μm, -Average Sdr:16.6%±15%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120.0 nm ± 40 nm, and -Average phosphorus content C P : in the range of from 2%, preferably from 3% to 5%, preferably to 6%.
[0056] The "±" (+ / -) values above and used hereinafter in this description are meant to indicate the range within which the physiochemical surface parameters are considered to vary, and are not meant to be tolerances of the measurements. The ranges and their boundaries so created are meant to be combinable with the boundaries of other ranges of the present invention and disclosure, and are meant to include all intermediate values.
[0057] Preferably, the surface characteristics of the apical, transitional and coronal implant regions are at least partially obtained, preferably by anodizing, and preferably the surface of said regions is an anodized surface comprising an oxide layer. This method is known to provide a high degree of flexibility in producing and designing highly durable surface oxide layers. Alternatively, sandblasting or acid etching can be used to produce the oxide layer of the present invention.
[0058] The surface of the transitional implant area and / or the periapical implant area is obtained, preferably by spark anodization. This process is a variant of anodization, using high voltage to generate sparks. The surface so treated is relatively rough, exhibits many open pores, has a high open porosity and has a crater / volcano-like structure. Using spark anodization is a way to roughen and structure the implant surface. This is beneficial for osseointegration, providing surface properties for bone tissue to grow and attach, thus holding the implant to the bone.
[0059] The substrate of the dental implant preferably comprises titanium or a titanium alloy, and optionally, the oxide layer on the surface of the apical and transitional implant regions preferably comprises crystalline titanium oxide in the anatase phase, preferably in the range of 70-100%, the remainder comprising rutile titanium oxide and / or amorphous titanium oxide. The use of titanium materials as the substrate of the dental implant is advantageous in that titanium and titanium alloys are well-known biomaterials that have been extensively studied and have proven high biocompatibility and suitable mechanical properties. The preferred anatase fraction contributes to good biocompatibility of the dental implant and promotes bone tissue integration, especially pronounced in the apical implant region.
[0060] Optionally, in contrast to the transitional and apical implant regions, the surface and surface oxide layer of the coronal implant region comprises mainly or entirely consists of amorphous titanium oxide. More preferably, the oxide layer of the coronal implant region, as well as the surface of the coronal region, is substantially amorphous and / or anatase-free. By substantially amorphous and / or anatase-free, it is meant that no statistically significant signal for crystalline phases and / or anatase is detected by X-ray diffraction, e.g., grazing incidence X-ray diffraction.
[0061] In a dental implant according to a preferred embodiment of the present invention, the coronal implant region extends from the coronal end of the dental implant along the longitudinal axis up to 2 mm ± 0.5 mm towards the apical end of the dental implant, the transitional implant region extends further along the longitudinal axis from 2 mm ± 0.5 mm up to 4 mm ± 0.5 mm towards the apical end of the dental implant, and the apical implant region extends from 4 mm ± 0.5 mm up to the apical end of the dental implant. The above description is essentially a definition of the spatial extent of the different implant regions along the dental implant, in particular along its length or longitudinal axis as defined above. As a result, the coronal implant region may have a length of about 2 mm starting from the coronal end of the dental implant. The transitional region may also have a length of about 2 mm, starting 2 mm away from the coronal end of the dental implant and ending about 4 mm away from its coronal end adjacent to the apical implant region. The apical implant region, following the transition region, begins at a position approximately 4 mm away from the coronal end of the dental implant and extends up to and including the apical end / apex of the dental implant. Alternatively, the coronal implant region has a length of 0.5 mm, preferably 1.0 mm, more preferably 1.5 mm, up to 2.5 mm, preferably 4.0 mm, more preferably 6.0 mm, measured from the coronal end of the dental implant along the longitudinal axis towards the apical end of the dental implant. As can be seen from this embodiment, the coronal implant region is not limited to a length of approximately 2 mm, but can be longer end, thus extending further from the coronal end of the dental implant along the longitudinal axis towards the apical end / apex of the dental implant. These options provide great flexibility in designing the dental implant surface with respect to the specifics of the implant scenario and the needs of the patient. For example, for long dental implants, a longer coronal implant region may be preferred. The same may be true if in situ and in vivo conditions require larger / longer areas of yellow color and / or increased washing capacity.
[0062] Components A further aspect of the present invention and disclosure is a dental component or dental component (preferably a dental abutment), the surface of the component being at least partially, preferably completely, covered by an oxide layer having an average thickness in the range of 60 nm to 170 nm and having an average arithmetic mean height Sa in the range of 0.05 μm to 0.5 μm.
[0063] The general term "component" as used herein is meant to include dental parts and dental devices other than the dental implant mentioned above. Thus, preferably, the dental implant and the component are different entities. Thus, in a preferred embodiment, the component is a dental component, and even more preferably, a dental abutment or a dental implant abutment. In traditional dentistry, an "abutment" is understood to be a separate entity used to mediate the connection between a dental implant and a dental restoration. Such parts as conventionally understood are included in the present invention and disclosure. Thus, the component may be a dental abutment as generally understood by those skilled in the art.
[0064] From the above, it can be seen that the surface of the component is quite similar to the surface of the coronal implant region of the dental implant described above, with the range of Sa being somewhat narrower and varying to lower values. Nevertheless, all explanations and definitions given above regarding the coronal implant region apply mutatis mutandis to the component. Therefore, in order to simplify this specification, the explanations and definitions are not explicitly repeated here, but each apply. This also applies explicitly to all optional component features described below, whose respective counterparts can be found in the optional dental implant features. Vice versa, the explanations given for the optional component features can be applied to each dental implant feature outlined above. The intended similarity between the surface of the coronal implant region and the surface of the component (abutment) means that all preferred and optional features described above for the coronal implant region (e.g. Ca, Mg, F content; amorphous, anatase free, etc.) can also be applied to the surface of the abutment, even if the features are not explicitly repeated here.
[0065] The above components and their surface design are advantageous in that they support soft tissue attachment, minimize bacterial accumulation and also minimize the grey shine-through effect through the soft tissue. The specific surface roughness Sa limits plaque formation and favors a stable soft tissue seal. The presence of an oxide layer supports epithelial cell attachment.
[0066] Preferably, the surface of the component is at least partially obtained by carrying out an anodizing treatment, preferably the surface of the component is an anodized surface comprising an oxide layer. Again, reference is made to the explanations provided for the respective properties of the coronal implant region, which apply here. In particular, in the case of an abutment substrate being titanium or a titanium alloy, which is an embodiment of the invention, anodizing may provide the titanium surface with antibacterial properties, thus reducing bacterial accumulation. Furthermore, the oxidized nanostructured titanium surface according to an embodiment of the invention promotes the attachment, proliferation and extracellular matrix secretion of human gingival fibroblasts compared to the as-machined surface. The abutment surface may also be obtained by acid etching and / or sandblasting, both of which are included in the present invention. Preferably, the oxide layer of the surface of the component is substantially free of amorphous and / or anatase. Substantially free of amorphous and / or anatase means that no statistically significant signals for crystalline phases and / or anatase are detected by X-ray diffraction, for example by grazing incidence X-ray diffraction.
[0067] In a further embodiment, the surface of the component is smooth, nanostructured, essentially non-porous and / or exhibits an as-machined structure, in particular including the arrangement of turning lines from the machining process, whereby the same advantageous surface structures, effects are obtained as described and illustrated above for dental implants, in particular the coronal implant region thereof.
[0068] Preferably, the surface of the abutment shows a yellow or pink color when viewed by the human eye and / or analyzed by a spectrometer. The above colors are also interference colors caused by an oxide layer on the surface of the component. The color can be adjusted by varying the thickness of the oxide layer, thus minimizing the gray shine-through effect through soft tissue and improving the in situ appearance. In the present invention and disclosure, the coloring is preferably achieved by anodization, and therefore each method may be called "yellow anodization" or "pink anodization" or the like. As indicated above, optionally, an oxide layer and therefore a coloring can also be provided on the inner surface of the dental implant or component, as described below. This may contribute to a better fixation of a screw or the like when inserted into a cavity having that inner surface.
[0069] Optionally, the surface of the component has an average arithmetic mean height Sa ranging from 0.08 μm, preferably from 0.13 μm to 0.3 μm, and further optionally, the oxide layer has an average thickness ranging from 80 nm to 130 nm, preferably to 150 nm, and more preferably to 160 nm. The narrower ranges further enhance the beneficial effects with respect to similarly designed coronal implant regions, as outlined above. The preferred values can be combined with each other, and all possible combinations are included in the present invention and disclosure.
[0070] In particularly preferred embodiments, the surface of the component exhibits at least one of the following, and preferably all of the following: -Average Sa: 0.2μm±0.1μm, -Average Sdr:5.0%±5%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120 nm ± 40 nm, and -Average phosphorus content C P : in the range of from 2%, preferably from 3% to 5%, preferably to 6%.
[0071] The "±" (+ / -) values above and used hereinafter in this description are meant to indicate the range within which the physiochemical surface parameters are considered to vary, and are not meant to be tolerances of the measurements. The ranges and their boundaries so created are meant to be combinable with the boundaries of other ranges of the present invention and disclosure, and are meant to include all intermediate values.
[0072] As previously mentioned, the substrate or bulk material of the component comprises, and preferably consists of, titanium or a titanium alloy for the same reasons and benefits as described for the coronal region of the dental implant, firstly because titanium-based materials are well-known and widely used biomaterials, and the use of such materials is particularly beneficial when anodization / anodization processes are used, resulting in a highly functionalized and useful titanium oxide layer on the surface of the component.
[0073] Implant System Yet another aspect of the present invention and disclosure is an implant system comprising or consisting of a dental implant as defined and described above and components as defined and described above. The innovative implant system is designed for a designed surface based on biological and clinical needs and subsequent design inputs. The dental implant and components are configured to be connectable to each other. In particular, when the components are dental abutments, the skilled person will understand that the dental implant and dental abutment are designed to be mutually combinable and connectable to each other. The two parts then complement each other to form an assembly. In many cases, the dental implant has a female shape (hole, recess, etc.) into which the male shape of the dental abutment can be inserted. Reverse shapes or screw or adhesive connections, etc. are also possible and are included in the present invention and disclosure. The above system thus combines all the benefits and advantages outlined above for each separate component in one assembly, thereby obtaining a novel implant system with overall superior properties. Dental implants and components with specially designed surfaces have been tested for cell attachment and proliferation, confirming successful cell attachment and proliferation when seeded onto the optimized designs.
[0074] Also part of this invention and disclosure is a kit of parts, meaning that the dental implant and components are provided free of charge, for example, in a sterile pouch or bag, ready to use, which can be supplemented with dental restoration parts, further described below, to form a three component kit of parts.
[0075] The surface morphology and / or the magnitude of the individual surface properties (i.e., physicochemical properties) of the coronal implant region and the component are preferably similar to each other. In other words, the present invention and part of this disclosure is an assembly or kit of parts, where the dental implant and the component (preferably, the dental abutment) match each other with respect to their surface properties. By "matching", it is preferably meant that the surface of the coronal implant region is more similar to the surface of the component than the surface of any one of the other regions, the transitional implant region, or the apical implant region. The similarity / similarity of the surface texture, chemical composition, oxide layer thickness, and nanostructure between the component surface and the coronal implant region allows for a smooth soft tissue transition from the component / abutment to the dental implant.
[0076] In other words, preferably the difference between the magnitude or value of the individual surface characteristics of the coronal implant region and the magnitude or value of the individual surface characteristics of the components is less than the difference between the magnitude or value of the individual surface characteristics of the apical implant region or the transitional implant region and the magnitude or value of the individual surface characteristics of the coronal implant region.
[0077] For example, when using a dental implant, at the surface of the dental implant, the coronal implant region exhibits at least one of the following, and preferably all of the following: -Average Sa: 0.5μm±0.3μm, -Average Sdr:16.6%±15%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120.0 nm ± 40 nm, and -Average phosphorus content C P : preferably in the range of from 2%, preferably from 3% to 5%, preferably to 6%, then the component (dental implant) is combined with phosphorus, the surface of the component exhibiting at least one of the following, preferably all of the following: -Average Sa: 0.2μm±0.1μm, -Average Sdr:5.0%±5%, - average nanostructure size: 80nm ± 50nm, - average oxide layer thickness d OX : 120 nm ± 40 nm, and -Average phosphorus content C P : in the range of from 2%, preferably from 3% to 5%, preferably to 6%.
[0078] Again, the "±" (+ / -) values above and used hereinafter in this description are meant to indicate the range within which the physiochemical surface parameters are considered to vary, and are not meant to be tolerances of the measurements. The ranges and their boundaries so created are meant to be combinable with the boundaries of other ranges of the present invention and disclosure, and are meant to include all intermediate values.
[0079] One of the preferred options for implant systems is a combination in which the dental implant is made from technically pure titanium and the components (abutments) are made from titanium alloys.
[0080] In a preferred embodiment, the implant system further comprises a dental restoration element, and the implant, the component and the dental restoration element are combined and connected to form an assembly. Optionally, the above three components form a dental component parts kit. The dental restoration element can be a crown, etc. Thus, the present invention and disclosure includes a complete system for replacing teeth by the technology of dental implantology, especially with the excellent properties resulting from the designed and adapted surfaces of the dental implants and components.
[0081] With regard to possible methods of producing the above-described dental implants (especially the surfaces of the transitional and apical implant regions), reference is made to the methods of modifying the surface of an implant in published documents WO00 / 72777A1 and WO01 / 76653A1. These documents can be used to produce dental implants according to the invention, in particular for the embodiments in which the dental implant or component comprises or consists of titanium or a titanium alloy. Preferably, the surface is therefore produced by anodization and spark anodization, whereby the as-machined surface of the implant is transformed into one with an oxide layer thereon. Spark anodization (i.e. anodization with high voltage) produces a rough surface with many crate-like characteristics as desired for the apical implant region. Usable electrolytes for anodization / anodization are H2SO4 and H3PO4 diluted in a heated acid or salt bath. Typical voltages for anodization / anodizing, especially for creating surfaces in the coronal region of dental implants and surfaces of components, are in the range of 30V-100V, preferably 55V-80V. Typical anodization duration / times are in the range of 20s-90s, preferably 30s-70s. Spark anodization, especially used for creating surfaces in the apical implant region, is carried out at voltages in the range of 240V-300V.
[0082] The drawings presented below are only exemplary, non-limiting schematic diagrams. [Brief description of the drawings]
[0083] [Figure 1] 1 illustrates several dental implant structures according to the present invention and disclosure. [Diagram 2] 1 illustrates component structures in the form of several dental abutments in accordance with the present invention and disclosure. [Diagram 3] 1 illustrates an implant system comprising a dental implant and a dental abutment according to the present invention and disclosure, along with microscopic images showing the surface characteristics and morphology of each part of the system. [Figure 4a]FIG. 4 shows a diagram of the surface properties and functions of the implantable or implant components in relation to the use of a protective layer according to the present invention. In this specification, the implantable or implant components are represented by an implant. FIG. 4a shows on the left side the state in which the protective layer has been formed on the implant surface. Air molecules such as water and hydrocarbons cannot reach the surface because the protective layer provides a physical barrier. In the center of FIG. 4a, it is shown how the protective layer quickly dissolves or disintegrates upon contact with bodily fluids. Any molecules adsorbed from the air are carried away while the protective layer dissolves or disintegrates. On the right side of FIG. 4a, the state of the implant is shown after the protective layer has dissolved or disintegrated to allow the implantable or implant components to interact with the surrounding tissue. It should be noted that in this exemplary embodiment, the implantable or implant components are made from a material with hydroxyl groups (OH) on the surface, such as titanium, which exhibits a highly hydrophilic surface (e.g., a water drop contact angle in the range of 0-30°). [Figure 4b] The carbon content resulting from hydrocarbons adsorbed from the surrounding atmosphere on the implant surface with and without a protective layer (PL) after a certain period of time is shown. [Figure 4c] Contact angle measurements of implants with contact angles of 46.3° (left, no PL) and 0° (right, with PL) are shown. [Figure 4d] The density of hydroxyl groups on the titanium surface that was not protected by PL (left) and that was protected by PL are shown. [Figure 4e] FIG. 1 shows the metabolic activity of implants provided with a protective layer of the invention (with PL) or without a protective layer of the invention (without PL) after 1, 3 and 7 days. [Figure 4f] FIG. 1 shows the metabolic activity of implants provided with a protective layer of the invention (with PL) or without a protective layer of the invention (without PL) after 1, 3 and 7 days. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0084] The examples detailed below are meant to be non-limiting: The invention and the above disclosure are not limited to the details of the following examples, which set forth only preferred methods of practicing the invention.
[0085] FIG. 1 shows several different designs of dental implants according to the present invention and disclosure. As can be seen, the dental implants can be screw-like or bone screws for insertion into the jawbone. A variety of different thread designs are possible, for example thread types that extend from the apical to the coronal end of the dental implant. The thread types can also vary along the longitudinal axis to provide different threads in different implant regions. For example, the threads in the apical region are different from the threads in the coronal region, thereby accommodating different retention needs in different tissues that the dental implant crosses. Retention means other than threads are also possible, for example, regular ridge structures with ridges perpendicular to the longitudinal axis. Also, the length and longitudinal extent of different regions of the dental implant can be different. In FIG. 1, the length of the coronal region is about 1 / 7 to 1 / 8 of the total length of the implant measured from the coronal end of the dental implant. FIG. 1 shows that the lighter color gives the coronal or color implant region a clearly different appearance from the rest of the dental implant, due to the different surface designs. In terms of color, the coronal implant region exhibits a gold color (i.e., a metallic yellow color), while pink is also conceivable. However, the other parts of the implant are matte gray. In the present example, the transition to the coronal region is substantially abrupt on a scale visible to the human eye. Exemplary FIG. 1b includes reference numbers that also apply to the dental implants of FIG. 1a and FIG. 1c. In FIG. 1b, the longitudinal axis L of the dental implant is shown, which is a longitudinal spatially extending extension of the dental implant. The upper end of the dental implant is formed by the coronal end 1. The apex or lower end of the dental implant is formed by the apical end 5. Three different regions are shown, as appropriate in the context, but are not limited to the range shown in FIG. 1b: the coronal implant region 2, the transitional implant region 3, and the apical implant region 4.
[0086] Figure 2 shows two design options for a component in the form of an abutment for use here with a dental implant. At the lower end of the dental implant one can see the shape provided for combination and connection with the appropriate dental implant. Looking at the colour, the abutment can be gold or metallic yellow in colour, depending on the individual parts of the abutment that are shiny or non-shiny.
[0087] FIG. 3 shows an implant system according to the invention, where each dental implant of screw type is combined with each component in the form of a dental abutment. Parts b, c, e, f, h, l, k and l show scanning electron microscope images at various magnifications. The apical or apical implant area shows a pronounced crate / volcano structure where the open pores on the surface reach opening sizes up to several micrometers. The surface is irregular and contains many randomly distributed surface structures. The adjacent transitional implant area shows similar crate / volcano-like and irregular morphologies. However, the surface characteristics and pores are smaller. A major change occurs in the coronal implant area, where the porous and irregular surface disappears and instead a regular pattern of lines or grooves resulting from the turning process can be seen. The above lines and grooves give the surface an oriented line roughness. At higher magnifications, a fine nanostructured surface is found. Here, essentially, the turned line structure is "decorated" by an oxide layer, which covers the turned line structure. Finally, turning to the dental abutment, it can be seen that in the embodiment shown, the surface morphology of the dental abutment is quite similar to that of the coronal implant region, exhibiting an array of turning lines / grooves superimposed by an oxide layer. Figure parts d, g, j and m show a 3D reconstruction of the surface shape obtained by white light interferometry, confirming the above observations.
[0088] The example shown in FIG. 3 may be elaborated below. The novel abutment surface was produced by turning followed by mild anodizing. The resulting surface is non-porous and smooth, with an average surface roughness Sa of 0.13±0.02 μm and a developed surface area ratio Sdr of 3.39% (see FIG. 3 b and d), showing regularly distributed nanostructures with a size of 69±48 nm and an oxide layer thickness of 153±5 nm (see FIG. 3 c). With regard to the thickness of the oxide layer, the abutment is given a yellow color (known as interference color), which has been shown to be beneficial in reducing the gray shine-through effect in case of thin mucosa. Due to the nanostructures created, and due to the approximately 20-fold increase in the thickness of the oxide layer compared to unmodified titanium, the created surface should favor the attachment of epithelial and fibroblast cells. Furthermore, the smooth surface is expected to control plaque retention and facilitate mechanical cleaning. The collar or coronal region of the dental implant (region 0-2 mm from the coronal end) has the least roughness, with Sa of 0.51 ± 0.03 μm and Sdr of 16.6%. As visible in Fig. 3 b and d, that roughness is obtained by adjusting the machine parameters, which results in a burr-free surface with defined dimensions and spacing of the turning lines. Moreover, the coronal implant region has similar characteristics to an abutment-like nanostructure with a size of 43 ± 21 nm and an oxide layer thickness of 142 ± 17 nm (see Fig. 3 f). The least rough surface, with Sa of 0.5-1.0 μm, shows slightly less bone loss compared to the smoother surfaces. Thus, the surface roughness of the implant collar / coronal implant region created herein needs to be at a reasonable level to balance the need for osseointegration with the need for maintenance and cleaning. Furthermore, the similarity in surface texture, chemical composition, oxide layer thickness, and nanostructure between the abutment surface and the coronal implant region allows for a smooth soft tissue transition from the abutment to the implant, as previously described. The body of the implant is gradually roughened by spark anodization.By varying the density and size of the standard volcano-like protrusions on the surface, the roughness is increased from Sa (0.92 ± 0.16 μm) in the transitional implant zone (i.e., 2-4 mm from the coronal end of the dental implant) to Sa (1.49 ± 0.19 μm) in the apical / apical implant region (4 mm - apex), more closely approximating the roughness known to elicit the best bone response in vivo. The increase in roughness from the transitional implant region to the apical implant region also increases the surface area, as reflected by the Sdr values of 148% and 187%, respectively. Overall, the increase in Sdr from the coronal end to the apical end is designed to be inverse to the decreasing bone density from the implant platform / coronal end to the apex and apical end. This increases friction toward the apex, allowing for proper implant retention. High currents exceeding the breakdown voltage used to roughen the surface of the transitional and / or apical implant regions result in the formation of oxide layers two orders of magnitude larger, reaching 7.2±0.3 μm and 9.9±1.3 μm in the transitional and apical implant regions, respectively. These oxide layers are anatase-rich and contain high surface energy and many free hydroxyl groups. Compared to sandblasted and acid-etched commercial implants, the anodized surfaces show the most hydroxyl groups. Highly hydroxylated titanium surfaces promote osseointegration and bone formation in vivo, possibly through favorable adsorption of ECM molecules, and improve mineralization and differentiation of osteoblasts. Anatase-rich anodized implant regions have optimized properties for osseointegration, leading to a more predictable treatment for various conditions and a lower failure rate than other surface modifications after functioning for more than 10 years. During growth, oxygen and phosphorus from the electrolyte are incorporated into the oxide layer. The abutment surfaces show an average of 3.49±0.36% phosphorus, while the coronal implant area surfaces show 4.00±0.13%, the transitional implant area 7.20±0.59% and the apical implant area 8.16±0.31%. In the table below the physiochemical surface properties of the various components and areas of the above mentioned implant systems are summarized. JPEG2025004210000002.jpg102166
[0089] In the following, the measurement methods used to determine the above physiochemical properties are described, which also provide examples of related measurement methods generally applicable for determining all parameters mentioned in this description.
[0090] The thickness of the oxide layer, d OX The thickness is measured on a cross section of the dental implant or component. To that end, the dental implant or component can be cold mounted in acrylic resin, ground and polished to achieve a cross section along its centerline or its longitudinal axis (defined below). The side of the dental implant or component can be imaged by scanning electron microscopy (SEM) and the thickness of the oxide layer at various positions of the SEM image is measured with the aid of software. This is a procedure well known to those skilled in the art. For the measurements carried out here, a Zeiss Leo 1530 scanning electron microscope, a secondary electron detector and a 5 kV acceleration voltage at various magnifications were used. The pore size and nanostructure were determined using ImageJ software and SEM images at magnifications of 1 k and 10 k, respectively. Six images were used per condition. Preferably, the above thickness of the oxide layer is an average thickness, meaning that this thickness is measured at various positions of the coronal implant area or any implant area involved and then the mathematical average calculated from all the measurements.
[0091] Roughness parameters Sa and Sdr The measurements were made using white light interferometry. Image stacks of the implant surfaces were acquired by an optical 3D profilometer, gbs, smart WLI extended (Gesellschaft fur Bild und Signalverarbeitung mbH, Ilmenau, Germany) using a 50x objective. The acquired data were then processed with MountainsMap® software to determine the surface roughness. The parameters Sa and Sdr were determined after applying a polynomial 3 removal form and a Gaussian filter with a 50 μm cutoff (FALG, ISO16610-61). The measurement area was 350 × 220 μm for all measurements. Four components and four dental implants were measured, with the dental implants measured in each of the nine areas for each region shown in Figure 3 (i.e., coronal, transition, and apical regions). The abutments were measured in each of the nine areas.
[0092] Phosphorus content C P and surface chemistry To determine the elemental composition of the surface, X-ray photoelectron spectroscopy (XPS) measurements were performed as follows: The samples were rinsed twice for 120 seconds with 10 mL of ultrapure water (type 1, resistivity of 18.2 MΩ.cm). The samples were then dried with a nitrogen gas flow and mounted on the XPS sample holder. Care was taken to expose the cleaned implants to the laboratory atmosphere for a minimum time. XPS measurements were performed by a Kratos Axis Ultra spectrometer using monochromated AlKα X-rays (1486.6 eV). Binding energy calibration of the Kratos Axis Ultra DLD XPS instrument (S / N: C332549 / 01) was performed on 18 July 2018 according to BS ISO15472 (2010). For each sample, a survey spectrum was acquired (pass energy = 160 eV) from an area of approximately 2 mm × approximately 1 mm, and from the survey spectra, the elemental composition of the surface was determined. Charge compensation is achieved using a magnetically focused electron beam as a bulk current. The standard photoelectron take-off angle used for the analysis is 90°, resulting in sampling depths in the range of 5-8 nm.
[0093] Pore size and nanostructure size The pore size and nanostructure size were determined based on SEM images of each surface. Conventional imaging software was used to measure the pore size and nanostructure size.
[0094] Method for forming a protective layer, use and implant or implantable component having a protective layer - Patents.com The inventors of the present invention have surprisingly found that the surfaces of implantable or implant components can be protected from contamination, for example during storage, by providing a protective layer formed from a relatively low pH solution as described below, which can be removed more quickly and more completely and / or can provide or maintain a surface condition of the implantable or implant component that is favorable for biological integration, as compared to layers formed by prior art techniques.
[0095] In one aspect, the present invention relates to a method for forming a protective layer on a surface of an implantable or implant component, the method comprising: a) applying a solution to a surface of the component, the solution having a pH of 6.8 or less at 25° C.; b) drying the solution applied in step a) to form a protective layer on the surface of the implantable or implant component.
[0096] As used herein and throughout the present invention, the term "solution" refers to a composition that is in a liquid state at 20° C. and 1 atmosphere.
[0097] In one embodiment, the solution comprises inorganic cations and inorganic anions in a solvated (dissolved) state. In the present invention, the terms "inorganic cation" and "inorganic anion" respectively refer to a charged species of an element or group of elements that together form a salt. Examples of inorganic cations are the cations of alkali metals, alkaline earth metals, and other metals. However, the term also includes cations of ammonium, boron, arsenic, tellurium, etc. In other words, "inorganic cation" can be described as including positively charged species that do not contain carbon.
[0098] The term "inorganic anion" includes any negatively charged species that does not contain a carbon atom. In one embodiment, the term "inorganic anion" includes anions of halogens (especially F, Cl, Br, I), anions containing nitrogen and oxygen atoms such as nitrates or nitrites, anions containing nitrogen and oxygen atoms such as sulfates or nitrites, and anions containing phosphorus and oxygen atoms such as phosphates, pyrophosphates, or phosphites. Incidentally, in the present invention, ions formed by dissociation of water (i.e., H + / H3O + and OH - ) are not included in the terms "inorganic cation" and "inorganic anion," respectively.
[0099] The terms "monovalent," "divalent," and "trivalent" refer to the charge of a cation or anion. An example of a monovalent cation is Na.+ or K + and alkali metals such as ammonium. An example of a monovalent anion is Cl. - and H2PO4 - Examples of divalent cations include Ca 2+ and Mg 2+ Examples of divalent anions include those of alkaline earth metals such as SO4 2- and HPO4 2- Examples of trivalent anions include, for example, PO4 3- Includes.
[0100] The solution may be an aqueous solution. As used herein, the term "aqueous" means that the solution comprises 50% or more by weight of the total composition of water, such as 70% or more by weight or 80% or more by weight, such as 90% or more by weight. Other co-solvents that may be optionally present in addition to water include water-miscible solvents, in particular alcohols and ketones, such as methanol, ethanol, isopropanol, 1-butanol, 2-butanol, or acetone. These co-solvents are generally present in an amount of less than 50% by weight, such as 30% or less by weight or 20% or less by weight of the total weight of the composition.
[0101] The solution may also be non-aqueous. This means that the solution may not contain water or may contain water in an amount less than 50% by weight of the total composition. In this case, the solvent may be selected from the group consisting of water-miscible solvents, in particular alcohols and ketones, such as methanol, ethanol, isopropanol, 1-butanol, 2-butanol or acetone. These may be used alone or in combination. The choice of solvent is determined primarily by the ease of handling and the ability to dissolve the components of the protective layer, but may also be influenced by other factors such as flammability or toxicity.
[0102] In one embodiment, there is no co-solvent and water is the only solvent. In a preferred aspect of this embodiment, the solution consists of water and inorganic salts in solution to form solvated cations and anions. Herein, the salts preferably include monovalent cations, for example salts of alkali metals, preferably sodium. In one embodiment, the cations in the solution are selected from sodium and magnesium, with other cations being absent from all cations in the solution or present in an amount of 10 mol % or less (e.g., 5 mol % or less) of all cations in the solution. Incidentally, throughout the present invention, the dissociation of water (i.e., H + / H3O + and OH - ) are ignored in calculating the relative and total amounts of cations and anions in solution because their concentrations determine the pH. In other words, in the present invention, the concentrations and amounts of anions and cations are expressed independently of the pH of the solution and are expressed as H + / H3O + and OH - are ignored in calculating the absolute and relative amounts of inorganic and organic cations and anions.
[0103] In one embodiment, the solution may or may not include organic components and additives, which in one embodiment may be selected from the group consisting of sugars, water-soluble polymers such as polyvinylpyrrolidone (e.g., number average molecular weights of 15,000 or less, or 10,000 or less), collagen, antioxidants or antifouling agents (such as BHT), pharma- ceutical active ingredients (such as vitamins), antibacterial or germicidal agents, and antibiotics.
[0104] The solution may or may not contain an organic salt. The term "organic salt" refers to a material that forms a cation and an anion upon dissolution and dissociation in water, where either the cation or the anion is an organic compound that contains carbon. Examples of such organic salts include sodium acetate, sodium acetylacetonate, sodium formate, etc., and quaternary ammonium salts such as pyridinium chloride, tetramethylammonium chloride, etc.
[0105] In one embodiment, the amount of organic components and additives is 10% by weight or less, such as 5% by weight or less, such as 2% by weight or less, of the total weight of the composition. In one embodiment, such organic components and additives are absent.
[0106] In one embodiment, the aqueous solution is free of organic salts and free of other organic compounds or additives. In a preferred aspect of this embodiment, the salts are formed exclusively by sodium and magnesium salts, more preferably sodium and magnesium phosphates, hydrogen phosphates, dihydrogen phosphates, and chlorides.
[0107] In one embodiment, the solution is + and H3O + In one aspect of this embodiment, the monovalent inorganic cation is Na + , K + , and NH4 + , preferably Na + and K + , more preferably Na + In the present specification, the amount of monovalent inorganic cations is preferably selected such that 50 mol % or more of the total inorganic cations are selected from monovalent inorganic cations, preferably 60 mol % or more, for example 65 mol % or more or 70 mol % or more of the total inorganic cations are selected.
[0108] Thus, in one embodiment, the amount of monovalent inorganic cations is 50 mol % or more, preferably 60 mol % or more, for example 65 mol % or more or 70 mol % or more of the total inorganic cations, and the monovalent inorganic cations are then Na + and K + In one embodiment, the monovalent inorganic cation is selected from the group consisting of Na + and Na + is present in an amount of 50 mol % or more, preferably 60 mol % or more, such as 65 mol % or more or 70 mol % or more of all inorganic cations.
[0109] In one embodiment, Na+ exists and K + is absent and the remaining inorganic cations are divalent inorganic cations, more preferably Mg 2+ and Ca 2+ , and even more preferably Mg 2+ In a preferred embodiment, the inorganic cation is selected from the group consisting of Na + and Mg 2+ The solution is formed only by Na + and Mg 2+ As used herein, Na + is preferably 50 mol % or more, preferably 60 mol % or more, such as 65 mol % or more or 70 mol % or more of the total inorganic cations.
[0110] The inorganic anion in the solution is not particularly limited, and any anion may be present, so long as it forms a salt with a cation that is readily soluble in body fluids. As a general guideline, salts that are soluble in water at 20° C. in an amount of 50 g / l or more, such as 100 g / l or more, 150 g / l or more, or even 200 g / l or more, may be used in the solution of the present invention, with highly soluble salts being preferred. Thus, the combination of anion and cation must be chosen such that low solubility salts are not formed, thereby making it possible to use salts that are not particularly soluble in body fluids, such as Mg. 2+ and Ca 2+ In the presence of divalent cations such as nitrate (NO3), carbonates and bicarbonates should be avoided, as this generally results in the formation of a precipitate of only the poorly soluble carbonate, which has a solubility of about 0.1 g / l at 20° C. Thus, in one embodiment, the anion is nitrate (NO3 - ), sulfate (SO4 2- ), halogens, especially chlorides (Cl - ), phosphate (PO4 3- ), hydrogen phosphate (HPO4 2- ), and dihydrogen phosphate (H2PO4 - ) was selected from the group consisting of:
[0111] In one embodiment, the solution comprises a salt selected from sodium and magnesium chlorides, phosphates, hydrogen phosphates, and dihydrogen phosphates, but does not include any other salts.
[0112] In one embodiment, the solution comprises sodium cations, which form 30-100 mol % (e.g., 50-99 mol %) of the sum of all alkali and alkaline earth metal cations in the solution, and the solution comprises phosphate, hydrogen phosphate, and / or dihydrogen phosphate anions, which form 30 mol % or more, such as 50 mol % or more, of the sum of all inorganic anions. As used herein, alkali metal cations include all cations of the metals in Group 1 of the periodic table (i.e., Li, Na, K, Rb, Cs, and Fr) except hydrogen, and alkaline earth metal cations include all cations of Group 2 of the periodic table (i.e., Be, Mg, Ca, Sr, Ba, and Ra).
[0113] In one embodiment, the solution comprises magnesium ions, preferably the magnesium ions form 0.1-50 mol % of the sum of all alkali and alkaline earth metal cations in the solution, the remainder may then be formed by sodium and potassium cations, preferably the remainder is formed by sodium cations.
[0114] In one embodiment, the solution is free of calcium ions, and preferably free of ammonium ions.
[0115] Surprisingly, the pH of the solution has a significant effect on the properties of the protective layer, and the protective layer formed from a solution with a pH of 6.8 or less (25°C) is superior in terms of removability and provides a highly hydrophilic surface (a surface with high surface energy) after dissolution of the protective layer. Both of these effects are believed to facilitate the incorporation of the implant or implantable component, since a purely highly hydrophilic implant or implantable component surface can be provided after dissolution of the protective layer. For example, when the implant or implantable component is made of a metal or metal alloy, in particular titanium or titanium alloy, the surface of the implant or implantable component after dissolution of the protective layer may exhibit a high density of hydroxyl groups, which is believed to facilitate integration with the surrounding tissue.
[0116] Although the effects are not yet fully understood and without wishing to be bound by theory, it is believed that the surface charge (e.g., of titanium or titanium alloy implant or implantable components) is strongly dependent on the pH of the solution in which it is immersed. At low pH, the surfaces of implant or implantable components (e.g., surfaces made of metals or metal alloys or surfaces made of metal oxides such as titanium oxide) are believed to be positively charged, and the surface charge gradually decreases in the solution as the pH increases. This is represented by the isoelectric point (i.e., the pH at which the positive and negative charges on the surface are balanced). For materials made of titanium, titanium alloys, and titanium oxide, the isoelectric point is generally comprised between pH 4.0 and 6.8.
[0117] If the surface is negatively charged, cations in solution will interact strongly with the surface and will be less likely to be washed away. Conversely, a positive charge may make the cations easier to remove, as they will be less attracted to the surface.
[0118] By using a protective layer solution with a pH of 6.8 or less, the interaction of the cations with the surface is weakened, which may explain the easier removal of the cations when rinsed with water or when contacted with body fluids. Therefore, preferably, the pH of the solution is also lower than the isoelectric point of the surface on which the protective layer is formed.
[0119] Furthermore, it can be assumed that a low pH of 6.8 or less can prevent or reduce the uptake of carbon dioxide and possibly other species from the atmosphere during the production of the protective layer and / or during storage of the implant or implantable component having the protective layer. When carbon dioxide is adsorbed, it forms carbonate and bicarbonate ions in the solution, which leads to the formation of salts with relatively low solubility, especially in combination with alkaline earth metal cations. Carbonates are also less hydrophilic materials and therefore can facilitate the adsorption of organic contaminants to the surface of the protective layer. Since the solution for forming the protective layer of the present invention reduces or prevents the formation of carbonates, the absence or reduced amount of less soluble carbonates can allow the protective layer to dissolve more rapidly, preventing or reducing contamination by organic substances. Therefore, this is another reason for the pH of the solution at 25°C to be 6.8 or less, for example 6.5 or less, 6.0 or less, 5.5 or less, or 5.0 or less.
[0120] Thus, in one embodiment, the pH of the solution at 25° C. is lower than the isoelectric point of the surface of the implant or implantable component and may be 6.8 or less, for example 6.5 or less, 6.0 or less, 5.5 or less, or 5.0 or less, depending on the metal or alloy used.
[0121] Also, while a strongly acidic solution solves the problem of the present invention, it may have the potential to cause adverse biological effects upon dissolution in the patient's body. Therefore, the pH of the solution is preferably 0.0 or more, 0.5 or more, or 1.0 or more, for example, 1.5 or more or 2.0 or more. Thus, the pH may be, for example, in the range of 2.8 to 3.4, 3.6 to 4.9, or 3.5 to 5.5.
[0122] Furthermore, due to its low pH, the protective layer maintains the amount of available functional groups (e.g. OH groups) on the surface of the implantable or implant component, for example made from titanium, during storage, which means that the protective layer is configured to reduce carbon deposition and maintain the hydrophilicity and / or density of free / unbound hydroxyl groups on the surface of the implantable or implant component during dry storage compared to storage without the protective layer.
[0123] The protective layer of the present invention therefore allows dry storage of the implant or implantable component. The present invention also encompasses the use of a protective layer obtained by drying a solution as described herein to protect the implantable or implant component from contamination during storage, preferably the implantable or implant component is in a dry state during storage.
[0124] The salt concentration of the solution is not particularly limited, but can be adjusted by one skilled in the art to obtain the desired thickness of the protective layer. In one embodiment, the solution has a total concentration of inorganic salts of 1-200 mM, 2-50 mM, or 5-20 mM, for example, 7-10 mM, expressed as the sum of all salts formed by inorganic cations and inorganic anions as described above.
[0125] The salt concentration can be as high as 2, 4, 5, 7, 10, 20, 40, or 50 mM or more, but as low as 180, 150, or 125 mM or less, within these ranges, a sufficiently thick salt layer can be formed by wetting or soaking the implant and then drying.
[0126] The protective layer formed from the above described solution protects the implantable or implant component from contamination during storage, meaning that the amount of contaminants is reduced compared to the implantable or implant component in the absence of the protective layer.
[0127] The protective layer also maintains the hydrophilicity of the implantable or implant component during storage. Thus, after removal / dissolution of the protective layer, the highly hydrophilic surface of the implantable or implant component can be maintained and exposed again. To achieve this, it is required that the surface must either be made hydrophilic (i.e. the free surface energy must be increased) before the solution is applied, or that it must be made hydrophilic simultaneously with the application of the solution. Thus, in one embodiment, the implantable or implant component exhibits a water contact angle of 0-30° both before the application of the solution in step a) and after removal of the protective layer, assessed by rinsing the implant or component with water at 25° C. for 2 minutes and then drying.
[0128] Consequently, in one embodiment of the method for forming a protective layer of the present invention, the method further comprises a step for increasing the free surface energy of the implantable or implant component prior to or simultaneously with the application of the solution in step a). This can be achieved by many methods known to those skilled in the art, such as acid etching with inorganic acids such as HF, HCl, H2SO4 or mixtures thereof, UV irradiation, oxidation with peroxides, plasma treatment, etc. Also, the methods described in EP0388576 may be used.
[0129] The protective layer formed from the solution as described above is easily removable when implanted. This can be assessed by testing the removal of the elements of the protective layer in a rinse test. In one embodiment, after rinsing the implant or component with water at 25° C. for 2 minutes (e.g. by placing the implant or component under a slow flowing stream of water), no more than 30 atomic % of the protective layer remains on the surface, such as no more than 20 atomic %, preferably no more than 10 atomic %. This can be assessed by any suitable surface analysis method, such as XPS or Auger.
[0130] The solution is applied in step a) and then dried in step b) The application can be done by any suitable technique, such as coating, spraying or dipping / immersing the implantable or implant components in the solution.
[0131] The following process parameters may be followed:
[0132] Process parameters during application: Temperature: Generally, 0 to 100°C, preferably 20 to 90°C o Pressure: Usually atmospheric pressure. o Time: A time that is sufficient to ensure complete wetting, for example, not less than 5 seconds, but generally not more than 5 minutes.
[0133] Process parameters during drying: Temperature: The temperature sufficient to allow drying is preferably between 30 and 95°C, more preferably between 50 and 90°C. Time: The time sufficient to achieve a dry state is preferably 15 to 120 minutes, more preferably 30 to 100 minutes. 〇 Pressure: Atmospheric pressure (below 1 atm), for example, 50 to 770 mmHg.
[0134] Generally, drying at moderate temperatures for longer periods and under relatively high pressure may be preferred to avoid the formation of highly porous layers that may not completely cover the implant surface.
[0135] The implantable or implant component is preferably made of, but not limited to, metals, metal alloys, plastic materials, and ceramic materials. Preferably, the implantable or implant component is made of a metal or metal alloy, with titanium and titanium alloys being particularly preferred.
[0136] The implantable or implant component is also not limited with respect to its form and shape, any implantable or implant component can be the subject of the methods and uses of the present invention. This includes, for example, hip implants, knee implants, implants designed as replacements for parts of an arm or leg, as well as dental implants and dental implant components such as abutments, crowns, bridges, etc. The implantable or implant component is preferably a dental implantable or implant component, more preferably a dental implant or a dental implant abutment. In one embodiment, the implantable or implant component can be an implant, an implant system, or a component also disclosed in the present disclosure.
[0137] The present invention not only includes the method for forming the protective layer and the use of the layer to protect components of an implant or implantable component during storage as described above, but it is also believed that the solution itself is an inventive contribution to the art. Thus, the solutions described above with respect to the method and use are considered to be claimable aspects of the invention, including all embodiments and preferred aspects of the solutions described above with respect to the method and use.
[0138] The thickness of the protective layer is not particularly limited, and a small thickness may be sufficient to obtain the desired protection. The thickness is determined by the concentration of the protective layer components in the solution and the amount of solution applied. The thickness may be 0.1 to 20 μm, for example, 0.2 to 5 μm or 0.3 to 3.1 μm.
[0139] The present invention also includes a package containing the implant or implantable components with a protective layer as described above. The package can be filled with dry implantable or implant components with an atmospheric protective layer selected from air, nitrogen, or other inert gas. Air can be used and the package does not need to be airtight, since the implant is protected by the protective layer. Optionally, sterilization, for example with ethylene oxide gas, can be used, which can be performed before packaging or even after packaging, since ethylene oxide gas permeates the package.
[0140] Example 1 - Effect of salt composition The effect of the salt composition was evaluated by formulating an aqueous solution containing only water as the solvent with the following composition:
[0141] solution 1 38.5mM Na2HPO4+7.15mM NaH2PO4+2.5mM MgCl2 solution 2 38.5mM K2HPO4+7.15mM KH2PO4+2.5mM MgCl2
[0142] Titanium implants were wetted with solution 1 or solution 2, respectively, and dried to obtain a salt layer on the implant.
[0143] To evaluate whether the salt layer could be removed by a simple washing process, each implant was rinsed three times with 10 ml of water. The elements of the remaining salt layer were then evaluated by Auger spectroscopy. It was seen that for the salt layer obtained from solution 1, 15% of the elements remained on the surface of the implant, while for the salt layer obtained from solution 2, 26% of the elements remained on the surface. This indicates that the sodium-based solution can be removed more easily than the potassium-based solution.
[0144] Example 2 - Effect of pH and surface energy To evaluate the effect of pH, Example 1 was performed by two modifications of solution 1 with the same salt concentration, but with pH 7.1 or pH 4.0, respectively. Again, after rinsing three times with 10 ml of water, the salt layer obtained from the pH 7.1 solution resulted in 15 atomic % of the elements remaining on the surface, while for the pH 4.0 solution, only 3 atomic % of the elements were attached to the surface.
[0145] This shows that adjusting the pH of the solution to acidic values makes it possible to obtain a layer that can be more easily and completely removed.
[0146] Further tests evaluated whether the surface energy of the implant substrate influenced the removability of the salt layer. Two tests were performed with solution 1, one with an implant with high surface energy (water contact angle = 0°) and one with a low surface energy (water contact angle = 47°). After rinsing the implants three times with 10 ml of water, for the implants with a large surface area, 15 atomic % of the elements of the salt layer remained on the surface, whereas for the implants with a low surface energy, only 2 atomic % of the elements remained on the surface. This indicates that the low surface energy of the implant's support structure surface facilitates removal.
[0147] Example 3 - Protection against contamination To test the effectiveness of the protective layer in protecting the surface from the adsorption of atmospheric elemental molecules, the carbon content was measured on the abutment surfaces stored in an environmental chamber (set at 25°C and 50% humidity) with or without a protective layer.
[0148] The abutment surfaces were UV ozone treated for 15 min, where applicable a protective layer formed from solution 1 above was applied and dried, and the resulting abutments were handled in the protective environment of a nitrogen-filled glove box (these samples are referred to as time 0). Samples with or without the protective layer were exposed to air for periods of 2 min, 1 h, or 3 days. The other samples, which were not UV cleaned first, were used as the final time point (t inf.). At each time point, the samples were rinsed with ultrapure water and blown dry with a stream of nitrogen. The carbon content of the surface is determined as atomic percentage by XPS or Auger spectroscopy (see also Figure 4b).
[0149] During storage, hydrocarbons and other atmospheric elements are deposited on the surface. Carbon accumulation was confirmed by evaluating the carbon content of 7.2 at% of the abutments cleaned with UV ozone. When exposed to atmospheric conditions, the carbon content increases rapidly to 13.4 at% after 2 min, 14.3 at% after 1 h, and 20.4 at% after 72 h. Interestingly, the carbon content is consistently lower when the abutments are exposed to the properties of the protective salt layer obtained from solution 1, reaching 12.4 at% after 72 h. The carbon content of the abutments stored in standard packaging without UV cleaning (at the final time point Inf) was also significantly lower when a salt layer was utilized compared to the abutments without a salt layer (14.6 at% vs. 34.9 at%, respectively). See also Figure 4b.
[0150] In addition to the carbon content, the ratios of other elements that make up the surface were not significantly different after rinsing the devices, indicating complete dissolution of the protective layer. This data suggests that the layer was indeed completely dissolved, exposing a pristine surface, as indicated by the low carbon levels after rinsing.
[0151] Furthermore, surface energy, which correlates with hydrophilicity, is known to decrease as air pollutants are deposited on the surface. Evaluation of the hydrophilicity of the stored samples confirmed the maintenance of high surface energy and hydroxyl groups as indicated by a contact angle of 0° compared to the sample stored without a protective salt layer (contact angle: 46.3±5.6°), confirming the lower carbon content and higher surface energy of the stored samples with the protective layer obtained from the solution of the present invention (see also FIG. 4c).
[0152] Finally, no differences in cell proliferation were observed in response to the protective layer, either for keratinocytes seeded on the abutments or for MSCs seeded on the implants (see Figures 4e and 4f, respectively), confirming the cytotropy of the protective layer.
Claims
1. 1. A method for forming a protective layer on a surface of an implantable or implant component, comprising: a) applying a solution to the surface of the component, the solution having a pH of 3.6 to 6.0 at 25° C.; and b) drying the applied solution of step a) to form the protective layer on the surface of the dental component; A method comprising:
2. The solution is H + and H 3 O + 2. The method of claim 1, comprising a monovalent inorganic cation other than and a monovalent, divalent, or trivalent inorganic anion.
3. The monovalent inorganic cation is Na + , K + , and N.H. 4 + is selected from the group consisting of Optionally, the monovalent, divalent, or trivalent inorganic anion is NO 3 - , S.O. 4 2- , Cl - , P.O. 4 3- , H.P.O. 4 2- , and H 2 P.O. 4 - The method of claim 2, wherein the compound is selected from the group consisting of:
4. The solution contains Mg 2+ and Ca 2+ , preferably Mg 2+ The method of claim 1 or 2, further comprising an inorganic divalent cation selected from:
5. The method according to any one of claims 1 to 4, wherein the pH of the solution is below 5.5 or below 5.0, for example from 3.6 to 4.
9.
6. the solution comprises sodium cations, the sodium cations forming 30 to 100 mol %, for example 50 to 99 mol %, of the sum of all alkali and alkaline earth metal cations in the solution; 6. The method according to any one of claims 1 to 5, wherein the solution comprises phosphate, hydrogen phosphate and / or dihydrogen phosphate anions, the phosphate, hydrogen phosphate and / or dihydrogen phosphate anions forming 30 mol % or more, such as 50 mol % or more, of the sum of all inorganic anions.
7. the solution comprises magnesium ions; 7. A method according to any one of claims 1 to 6, wherein preferably the magnesium ions form 0.1 to 50 mol % of the sum of all alkali and alkaline earth metal cations in the solution, preferably the solution is free of calcium ions and more preferably free of ammonium ions.
8. The method of any one of claims 1 to 7, wherein the solution has a total concentration of inorganic salts of 1 to 200 mM, 2 to 50 mM, or 5 to 20 mM.
9. The method according to any one of claims 1 to 8, wherein the protective layer protects the implantable component or components of the implant from contamination during storage.
10. 10. The method according to any one of claims 1 to 9, wherein the protective layer maintains the hydrophilicity of the implantable or implant component during storage, the implantable or implant component exhibiting a water contact angle of 0 to 30° both before the application of the solution in step a) and after rinsing the component with water at 25°C for 2 minutes and subsequent drying of the solution.
11. 11. The method according to any one of claims 1 to 10, further comprising a step for increasing the free surface energy of the implantable component or of the implant prior to or simultaneously with the application of the solution in step a).
12. The method according to any one of claims 1 to 11, wherein the protective layer maintains the amount of available functional groups on the surface of the implantable or implant component during storage.
13. 13. The method of any one of claims 1 to 12, wherein the protective layer is configured to reduce carbon deposition and maintain the hydrophilicity and / or density of free / unbound hydroxyl groups of the surface of the implantable component or implant component during dry storage compared to storage without the protective layer.
14. The method according to any one of claims 1 to 13, wherein the implantable component or implant component is a dental component such as a dental implant or an abutment, preferably a dental implant.
15. said implantable component or said implant component is a dental implant or a dental component, preferably a dental abutment, The dental implant comprises a coronal implant region, the surface of the coronal implant region comprising: at least partially covered with an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.1 μm to 1.0 μm; The surface of the dental component comprises: at least partially covered by an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.05 μm to 0.5 μm; The method of claim 14.
16. The method according to any one of the preceding claims, wherein the implantable component or the implant component is made from a metal or a metal alloy, preferably titanium or a titanium alloy.
17. An implantable or implant component having a protective layer obtainable by the method according to any one of claims 1 to 16.
18. Use of a protective layer obtained by drying the solution defined in any one of claims 1 to 8 for protecting implantable or implant components from contamination during storage, comprising: Preferably, the implantable component or components of the implant are dry during storage.
19. said implantable component or said implant component is a dental implant or a dental component, preferably a dental abutment, The dental implant comprises a coronal implant region, the surface of the coronal implant region comprising: at least partially covered with an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.1 μm to 1.0 μm; The surface of the dental component comprises: at least partially covered by an oxide layer having an average thickness in the range of 60 nm to 170 nm; having an average arithmetic mean height Sa in the range of 0.05 μm to 0.5 μm; 20. The use according to claim 18.
Citation Information
Patent Citations
Metallic transplantation piece
JP1991047264A
Devices with osteoinductive and osteoconductive properties
JP2005509494A
Abutment with hydroxylated surface
JP2007252897A
Coated implants, their manufacture and use
JP2007527758A
Strontium ion-containing bone tissue implants
JP2010533012A